PENGARUH PENERAPAN UNDANG-UNDANG PERLINDUNGAN ANAK TERHADAP PEMBERIAN PUNISHMENT KEPADA PESERTA DIDIK DI SMAK SINT CAROLUS KUPANG - Heu, Kristina Maria Puu; Bele, Graciana Amanda; Ngongo, Maria Hendritha Lidya; Tukan, Antonius Ignatius Nggino; Bria, Bonefantura Jemy (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2024)
This study aims to examine the effect of the implementation of the Child Protection Law on the practice of giving punishment at Sint Carolus Catholic High School, Kupang. This study uses a quantitative method with a descriptive correlational approach. The results of data analysis using descriptive techniques indicate that the implementation of the Child Protection Law at Sint Carolus Catholic High School, Kupang is very good (93.13%) and the giving of punishment is very good (90.21%). In addition, the results of a simple linear regression analysis show a significant positive effect between the implementation of the Child Protection Law and the giving of punishment (regression coefficient = 0.922, p < 0.05). Even though there is an effect between these two variables, the most important thing to note is that the use of punishment in education must be educational and not exceed the limits regulated by the Child Protection Law. This finding illustrates that although punishment at Sint Carolus Catholic High School, Kupang is implemented well, it is necessary to continue to monitor it so as not to violate children's rights. The implications of this study suggest the need for a more careful approach in giving punishment in order to be in accordance with the objectives of educating and protecting children.